2003
DOI: 10.1139/w03-047
|View full text |Cite
|
Sign up to set email alerts
|

Wild-type Escherichia coli producing microcins B17, D93, J25, and L; cloning of genes for microcin L production and immunity

Abstract: For the first time, an Escherichia coli strain producing four microcins (Mcc), B17, D93, J25, and L, and showing immunity to Mcc V was isolated and characterized. Each of the gene clusters encoding the production of Mcc B17, D93, and L was cloned separately. The gene cluster for Mcc L was cloned within a 13.5-kb HindIII-SalI fragment, which includes the Mcc V immunity gene, cvi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Comparison of its deduced sequence with those in databases revealed that the protein encoded is nearly identical to the cvi gene product, the immunity MccV protein, differing by a single amino acid at position 34. This finding correlates with the experimental finding that the wild-type E. coli LR05 is not sensitive to an MccV-producing strain (41). Thus, the substitution of residue 34 (Gly3Glu) does not modify the immunity protein activity.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Comparison of its deduced sequence with those in databases revealed that the protein encoded is nearly identical to the cvi gene product, the immunity MccV protein, differing by a single amino acid at position 34. This finding correlates with the experimental finding that the wild-type E. coli LR05 is not sensitive to an MccV-producing strain (41). Thus, the substitution of residue 34 (Gly3Glu) does not modify the immunity protein activity.…”
Section: Resultssupporting
confidence: 87%
“…A 13.5-kb HindIII-SalI DNA fragment issued from DNA plasmid was cloned into pUC19, resulting in pL102. It directs the production of MccL and immunity to MccL and MccV (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mcnR gene encodes for a putative regulator of 144 amino acids and shares 99% (143/144) identity with proteins ACA51174 from S. enterica ssp. This may explain why, despite their high similarity, microcin E492 and microcin N producers do not have cross-immunity (Sable et al, 2003). Between residues 19 and 142, McnR has a histone-like nucleoid protein (H-NS) domain (PRK10328).…”
Section: Microcin N Genetic Elementsmentioning
confidence: 99%
“…In most cases, further experiments would have to be performed in order to demonstrate with absolute certainty that the antimicrobial activities observed are indeed due to halocin biosynthesis. Besides, in the few cases for which the proteinaceous nature of the compound has been demonstrated, one cannot preclude the possibility that these halocins are in fact redundant with other known halocins, as observed in the case of HalH4 [29] or bacteriocins [52,53]. Halocins H2, H3 and H5 have been reported to be produced by the uncharacterized halophilic strains GLA22, GAA12 and MA220, respectively, all being isolated from a solar saltern in Alicante in Spain [21].…”
Section: Other Putative Halocinsmentioning
confidence: 99%